The Impact of Using Salt on Drying Rate of Fish - Delima, Rika; Sahira, Safinaz; Sumiroyani, Sumiroyani; Kamelia, Kamelia; Reskiana, Reskiana; Rahmi, Khusnul Aulia; Marta, Eni (International Journal of Natural Science and Engineering, 2021)
Fish drying by using additional salt as a preservative and adding flavor to the fish. This study aims to determine the effect of various doses of salt on the quality of tilapia, motan, dried salted lemongrass and the difference that does not use salt on the quality of fish. This type of research is quantitative research with experimental methods. The independent variable in this study was the concentration of NaCl salt as a treatment, namely 10%, 20%, 30% of the total fish weight. The controlled variables of this study were the type of fish, weather conditions, and materials used. The research process begins with weeding motan, tilapia, and lemongrass fish, namely motan fish, tilapia, and lemongrass fish, weighing 100 grams. Then the fish are weeded with running water, removed all the contents of the fish's stomach, and drained until the fish does not contain too much water. Then the addition of salt to the motan fish, tilapia, and lemongrass fish has been given, namely, 27%, 34%, and 41%. The duration of soaking or salting is 24 hours. After the salting time has been completed, the fish drying process is continued. The fish dried at a temperature of 30C to 35C for 2 to 3 days to obtain the desired characteristics of salted fish. Data was collected by testing the salt content in fish with different concentrations. The results showed a difference between salted fish and unsalted fish. Salted fish has a harder texture, taste better, and have a longer shelf life.